Answer:
![3x+\frac{7}{6}y](https://tex.z-dn.net/?f=3x%2B%5Cfrac%7B7%7D%7B6%7Dy)
Step-by-step explanation:
To simplify the expression, we first open the parenthesis, then we collect all the like terms. Lastly we simplify the like terms to its simplest form. Given that:
![\frac{1}{2}(3x-\frac{2}{3} y)+3(\frac{x}{2}+\frac{1}{2}y )\\\\Firstly, we\ expand\ the\ parenthesis:\\\\=\frac{1}{2}(3x)-\frac{1}{2}(\frac{2}{3} y)+3\frac{x}{2}+3(\frac{1}{2} y)\\](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D%283x-%5Cfrac%7B2%7D%7B3%7D%20y%29%2B3%28%5Cfrac%7Bx%7D%7B2%7D%2B%5Cfrac%7B1%7D%7B2%7Dy%20%29%5C%5C%5C%5CFirstly%2C%20we%5C%20expand%5C%20the%5C%20parenthesis%3A%5C%5C%5C%5C%3D%5Cfrac%7B1%7D%7B2%7D%283x%29-%5Cfrac%7B1%7D%7B2%7D%28%5Cfrac%7B2%7D%7B3%7D%20y%29%2B3%5Cfrac%7Bx%7D%7B2%7D%2B3%28%5Cfrac%7B1%7D%7B2%7D%20y%29%5C%5C)
![=\frac{3}{2}x-\frac{1}{3}y +\frac{3}{2}x+\frac{3}{2} y\\\\ Collecting\ like\ terms:\\\\=\frac{3}{2}x+\frac{3}{2}x-\frac{1}{3}y+\frac{3}{2}y\\\\Adding \ terms:\\\\=3x +\frac{7}{6}y](https://tex.z-dn.net/?f=%3D%5Cfrac%7B3%7D%7B2%7Dx-%5Cfrac%7B1%7D%7B3%7Dy%20%2B%5Cfrac%7B3%7D%7B2%7Dx%2B%5Cfrac%7B3%7D%7B2%7D%20y%5C%5C%5C%5C%20%20Collecting%5C%20like%5C%20terms%3A%5C%5C%5C%5C%3D%5Cfrac%7B3%7D%7B2%7Dx%2B%5Cfrac%7B3%7D%7B2%7Dx-%5Cfrac%7B1%7D%7B3%7Dy%2B%5Cfrac%7B3%7D%7B2%7Dy%5C%5C%5C%5CAdding%20%5C%20terms%3A%5C%5C%5C%5C%3D3x%20%20%2B%5Cfrac%7B7%7D%7B6%7Dy)
Open interval<span> is an interval that does not contain its endpoints</span>
Let the perimeter be x.
3x = 75 - 2x
Add 2x from both sides:
5x = 75
Divide both sides by 5:
x = 15
Answer: The perimeter is 15 units.
Answer:
x = 121
Step-by-step explanation:
The exterior angle of a triangle is equal to the sum of the opposite interior angles
x = 74+47
x =121
<span>(x - 2)(x - 3) = 2
x^2 - 2x - 3x + 6 - 2 = 0
x^2 - 5x + 4 = 0
(x -4)(x - 1) = 0
x - 4 = 0; x = 4
x - 1 = 0; x =1
{1,4}
answer
</span><span>{1, 4}</span>